The Attribution and the Concept of Breaking the Agreement According to the Scholars - Mohammad, Sabah H.; Jarjees, Halat H. (Humanities Journal of University of Zakho, 2018)
This study addressed the issue of breaking the agreement between the described and the describer and its semantic implication. The study showed how impressive the connotations of the attribution were when the expressions were brief and the agreement was broken, the thing that is not found in the regular use of the attribution. It is known that in the attribution the describer (adjective) follows the described and agrees with it in all its cases, so as to modify it. The agreement usually includes: the definite article, the number, the gender, and the case. However, sometimes the describer does not agree with the described, and the agreement may break in one or more incidents and in particular positions defined by some scholars. Nevertheless, the scholars did not mention all the positions or all the situations of this phenomenon; instead they mentioned only the break of agreement in the case issue stating that it is simply a divergence and a kind of mismatching. For this specific reason the current study aimed at collecting all the other situations in which the agreement between described and the describer were broken, to recognize the reason behind it and to identify why it occurs. The study as well amid at inspecting the difference between the attribution (na’t) and adjective (sifa) to see if there is any difference between them and whether the deference affects the agreement between described and the describer. This study included a preliminary that identified the attribution (na’t) and adjective (sifa) and the breaking of the agreement. The preliminary was followed by four sections organized according to the positions in which the breaking of the agreement occurs; the first section included the breaking of agreement related to the definite and the indefinite; the second section concentrated on the braking of agreement of gender; the third section dealt with the issue of breaking the agreement of the number with all its types and positions; and the fourth section examined the braking of agreement in the case situation which included, by itself, many subsections to end with a conclusion of the results of the research.